Flow cytometry methods for targeted isolation of ctenophore cells - Abigail C. Dieter; Aliyah B. K. True; Emily A. Gilbertson; Grace Snyder; Adam Lacy-Hulbert; Nikki Traylor-Knowles; William E. Browne; Lauren E. Vandepas (Frontiers in Marine Science, 2023)
Cell suspension fluidics, such as flow cytometry (FCS) and fluorescence-activated cell sorting (FACS), facilitates the identification and precise separation of individual cells based on phenotype. Since its introduction, flow cytometry has been used to analyze cell types and cellular processes in diverse non-vertebrate taxa, including cnidarians, molluscs, and arthropods. Ctenophores, which diverged very early from the metazoan stem lineage, have emerged as an informative clade for the study of metazoan cell type evolution. We present standardized methodologies for flow cytometry-mediated identification and analyses of cells from the model ctenophore Mnemiopsis leidyi that can also be applied to isolate targeted cell populations. Here we focus on the identification and isolation of ctenophore phagocytes. Implementing flow cytometry methods in ctenophores allows for fine scale analyses of fundamental cellular processes conserved broadly across animals, as well as potentially revealing novel cellular phenotypes and behaviors restricted to the ctenophore lineage.